Biodiversity associated with the rice field ageo-ecosystem in Asian countries : - Bambaradeniya, Channa N. B. (International Water Management Institute, 2004)
The book is to provide a synthesis that would enable us to better appreciate the environmental services and opportunities for biodiversity conservation offered by rice fields, as the additional benefits and contribution of these major food-producing agroecosystems.